TINDAK PIDANA PENGGELAPAN AKIBAT WANPRESTASI TIDAK MELAKUAN PEMBAYARAN KEPADA PERUSAHAAN PT. AGUNG BUMI LESTARI (Studi Putusan Pengadilan Negeri Tebing Tinggi No. 74/Pid.B/2019/PN.Tbt tertanggal 28 Mei 2019) - Oloan Sirait (Jurnal Smart Hukum (JSH), 2023)
In an agreement, there is a default. Sometimes defaults lead to criminal acts as stated in the decision of the Tebing Tinggi District Court No. 74/Pid.B/2019/PN.Tbt where the defendant is a customer of PT. Agung Budi Lestari after maturity did not hand over the amount of money from the sale of goods belonging to PT. Budi Agung Lestari, therefore the defendant was reported on charges of embezzlement. This study uses a normative juridical method because it examines the laws and regulations that are doctrinal in nature with a case approach and a conceptual approach which are then analyzed descriptively qualitatively. The results of the research on the legal regulation of the criminal act of embezzlement due to default where embezzlement is a crime regulated in Article 372 of the Criminal Code. The occurrence of no crime in default in the Tebing Tinggi District Court Decision No. 74/Pid.B/2019/PN.Tbt is due to an agreement relationship between the defendant and PT. Agung Budi Lestari but in practice the defendant did not fulfill what was agreed upon, namely to deposit a sum of money from the goods belonging to PT. Agung Budi Lestari who is under the control of the defendant. The application of default and criminal acts of embezzlement in the decision of the Tebing Tinggi District Court No. 74/Pid.B/2019/PN.Tbt wherein the decision stated that the defendant was guilty of violating the criminal provisions of Article 372 of the Criminal Code of embezzlement and sentenced to imprisonment for 2 (two) months. The application of the law to this case is wrong in imposing a verdict of guilty of committing a criminal act of embezzlement where the convict should be sentenced to acquittal as there has been jurisprudence on the same case in which the judge released the Defendant from all lawsuits in which there was a reason for the abolition of the crime so that it must be resolved. through civil court, not criminal.